Direct Laser-Driven Electron Acceleration and Energy Gain in Helical Beams. (1st June 2021) - Molnár, Etele; Stutman, Dan
Abstract : A detailed study of direct laser-driven electron acceleration in paraxial Laguerre–Gaussian modes corresponding to helical beams LG 0 m with azimuthal modes m = 1, 2, 3, 4, 5 is presented. Due to the difference between the ponderomotive force of the fundamental Gaussian beam LG 00 and helical beams LG 0 m, we found that the optimal beam waist leading to the most energetic electrons at full width at half maximum is more than twice smaller for the latter and corresponds to a few wavelengths Δ w 0 = 6, 11, 19 λ 0 for laser powers of P 0 = 0.1, 1, 10  PW. We also found that, for azimuthal modes m ≥ 3, the optimal waist should be smaller than Δ w 0 < 19 λ 0 . Using these optimal values, we have observed that the average kinetic energy gain of electrons is about an order of magnitude larger in helical beams compared to the fundamental Gaussian beam. This average energy gain increases with the azimuthal index m leading to collimated electrons of a few 100 MeV energy in the direction of the laser propagation.